Mobilizing Science, Technology and Innovation (STI) for Socio-Economic Development: The Experience of Malaysia - Kanagasundram Thiruchelvam (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
Malaysia has achieved remarkable economic growth for most parts of its history but is finding itself dogged by weak technological dynamism due to structural features of the economy as well as less than satisfactory proficiency in science, technology and innovation (STI). Despite massive investments in creating STI infrastructure, education, physical infrastructure and incentives to support technology upgrading, the stark reality is that the country continues to lag behind the successful latecomers. This paper presents a brief overview on Malaysia’s STI achievements, salient features of the nation’s national innovation system (NIS), the key challenges of its NIS and some recommendations on moving forward. The central theme of the paper is that success in STI is not automatic. It must be made to happen through effective policies promoting innovation as well as innovations in policy-making itself. Key words: Malaysia; national innovation system; STI; innovation; policy making